Improving the growth of oil palm seedlings by combining arbuscular mycorrhizal fungi and Trichoderma harzianum - Abd Malik, Mohd Nazif Saifuddin; Othman, Radziah; Yusuf, Umi Kalsom (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
Arbuscular mycorrhizal (AM) fungi and Trichoderma harzianum have shown beneficial effects on plant growth. The following study was conducted to investigate the growth performance of oil palm seedlings inoculated with both AM and T. harzianum. Nursery trial was arranged in a completely randomized block design (CRBD) consisting of five treatments in three replicates with ten palms per treatment (5 treatments x 3 replicates x 10 palms). The treatments were (i) Glomus sp., (ii) T. harzianum infused-compost, (iii) mixture of Glomus sp. with T. harzianum infused-compost, (iv) chemical fertilizers and (v) control. Three months old oil palm seedlings were planted into polybags containing ten kg of soil with the respective treatments. Results showed that seedlings treated with T. harzianum infused-compost had highly significant effects on stem girth, frond number, frond length, pinnae number, shoot and root dry weight and leaf area. The overall growth performances in descending order were T. harzianum infused-compost > mixture of Glomus sp. with T. harzianum infused-compost > Glomus sp.> chemical fertilizers > control. This study indicates that a mixture of Glomus sp. with T. harzianum infused-compost were relatively compatible, but T. harzianum infused-compost applied on its own still gave the best overall vegetative growth.